Research focused on microRNAs: a link between myocardial remodeling and growth during pathological processes and physical exercises - Kyselovič, Ján; Varga, Ivan (Annals of Translational Medicine, 2017)
Chronic heart failure has been classified as a global epidemic of the 21st century according to the recent report of American Heart Association Statistics Committee and Stroke Statistics Subcommittee (1). This diagnose is on the rise despite the recent advances in cardiovascular experimental and clinical sciences. More than 2% of the European population suffers from it and 30–40% of patients die within 1 year after receiving the diagnosis. Even with the very best of modern therapy, heart failure is still associated with an annual mortality rate of 10%, and it consumes 2% of the National Health Service budget in United Kingdom (2).